Serpulidae from the Albian–Cenomanian (Cretaceous) of Mexico - Vinn, Olev; Espinosa, Catalina Gómez; Bahena, Daniel Aviléz; García, Fatima L. Campos; Talavera-Mendoza, Oscar (Geologos, 2024)
Two serpulid species, Protula? antiquata? and Propomatoceros? sp., are recorded from the Morelos Formation (mid-Cretaceous) in Mexico. Serpulid tube structure is microcrystalline; the examined tubes are slightly diagenetically altered, but growth layers are well preserved. The short, straight growth layers with slightly curved distal ends in Protula? antiquata? occur also in some other serpulids such as the genus Josephella. The Mexican serpulid tubes are of a calcitic composition. The diversity of the present serpulid association is low for shallow tropical seas of the Cretaceous in comparison to rich assemblages recorded from Europe. The low diversity presumably results from some local environmental conditions such as rapid sedimentation and low nutrient content of sea water.